2022
DOI: 10.1039/d1en01032h
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the halloysite clay nanotube lumen for environmental remediation: a review

Abstract: Halloysite nanotubes (HNTs) are a naturally occurring clay mineral that have attracted much attention in recent years. Manipulating the lumen of halloysite nanotubes to take full advantage of its unique...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 175 publications
0
14
0
Order By: Relevance
“…23 Moreover, its peculiar tubular aluminosilicate structure enables H to be variously functionalized (external, internal, and interlayer surfaces), thus making it highly versatile. 17,24 Finally, H has been proved to show low toxicity. 25 Specifically, in this work, we used different crosslinkers for the L functionalization with H. The new cellulosic composites were characterized by several techniques (Fouriertransform infrared spectroscopy, thermogravimetric analysis, highresolution transmission electron microscopy, and tensile tests).…”
Section: Introductionmentioning
confidence: 99%
“…23 Moreover, its peculiar tubular aluminosilicate structure enables H to be variously functionalized (external, internal, and interlayer surfaces), thus making it highly versatile. 17,24 Finally, H has been proved to show low toxicity. 25 Specifically, in this work, we used different crosslinkers for the L functionalization with H. The new cellulosic composites were characterized by several techniques (Fouriertransform infrared spectroscopy, thermogravimetric analysis, highresolution transmission electron microscopy, and tensile tests).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the kaolinite as a major component of the samples did not show a significant increase in SSA compared to the halloysite-rich samples. It is reported that the etching effect caused by the availability of H + dissolves Al from the octahedral layer, resulting in an increasing internal surface area . Considering this, one would expect that the acid-treated LRS_H sample should provide quite an increased SSA (Table ).…”
Section: Resultsmentioning
confidence: 98%
“…It is reported that the etching effect caused by the availability of H + dissolves Al from the octahedral layer, resulting in an increasing internal surface area. 36 Considering this, one would expect that the acid-treated LRS_H sample should provide quite an increased SSA ( Table 4 ). The SSA of this acid-treated sample was only 10 m 2 /g from the original value of ca.…”
Section: Resultsmentioning
confidence: 99%
“… 18 Adsorption on MMT commonly occurs through cation exchange with sodium located inside of the material galleries; 19 in the case of HNT, hosting occurs via the diffusion of the pollutant inside of the lumen. 20 The poor performance recorded with graphite was surprising given the similarities of its molecular structure to that of graphene oxide. However, in graphite, the sheets are stacked in a layered fashion, making the diffusion of pollutants difficult.…”
Section: Resultsmentioning
confidence: 99%